Reconfigurable Hardware-based Embedded Control System Development using LabView Environment - SZÁSZ Csaba (Journal of Electrical and Electronics Engineering)
In recent years embedded systems gains attractiveness over traditional computer-based systems in many industrial applications. Usually embedded systems are optimized for a particular task and function. They express many advantages in terms of performance, cost-effectiveness, reliability, size-weight, or interfacing versatility over other computing solutions. This paper presents a specially developed reconfigurable hardware technology-based embedded system designed for a large scale of industrial control purposes. The software framework of the system has been developed in LabView graphical software environment. The final prototype of the conceived embedded system built upon a high performance FPGA-based development board has been tested in laboratory conditions. There, in a first step a simple dc motor control algorithm has been implemented, similar to many other motors control tasks that may be found in a wide range of practical applications of modern industry. As a result, the laboratory setup embedded system expresses a compact and modular structure, high operational precision, respectively real-time task execution abilities. In addition, the used last-generation reconfigurable hardware technology allows it huge flexibility and versatility in interfacing to many other hardware interfaces and industrial modules. Therefore, the presented design methodology and implemented setup may constitute a useful start point for other future developments. As well as, to provide ideas and guidance for researchers how to conceive and implement a large scale of high performance modern embedded systems.